Kunihiko Kodaira, Volume II : Collected Works - Kodaira, Kunihiko (Book collections on Project MUSE., 2015)
Kunihiko Kodaira's influence in mathematics has been fundamental and international, and his efforts have helped lay the foundations of modern complex analysis. These three volumes contain Kodaira's written contributions, published in a large number of journals and books between 1937 and 1971. The volumes cover chronologically the major periods of Kodaira's mathematical concentration and reflect his collaboration with other prominent theoreticians. It was in the second period that Kodaira did his fundamental work on harmonic integrals. The third period is chiefly characterized by the application of harmonic integrals and of the theory of sheaves to algebraic geometry and to complex manifolds. Originally published in 1975. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.